Cumulative Live Birth Rates of Good and Low Prognosis Patients According to POSEIDON Criteria: A Single Center Analysis of 18,455 Treatment Cycles - Shi, Wenhao; Zhou, Hanying; Tian, Li; Zhao, Zhenghao; Zhang, Wei; Shi, Juanzi (Frontiers in Endocrinology, 2019)
Objective: To investigate the characteristics and outcomes of low prognosis patients defined by POSEIDON criteria undergoing IVF treatment. Design: Retrospective cohort analysis. Setting: An IVF clinic in a public hospital. Patients: 18,455 fresh aspirated IVF cycles with subsequently frozen embryo transfer from Jan 2014 to Jan 2017 in a single IVF clinic were included in the analysis. The low prognosis patients were categorized into 4 groups based on POSEIDON criteria: group 1: age < 35, antral follicle count (AFC) ≥ 5, number of oocytes retrieved ≤ 9 in the previous cycle; group 2: age ≥ 35, AFC≥5, number of oocytes retrieved ≤ 9 in the previous cycle; group 3: age < 35, AFC < 5; group 4: age ≥ 35, AFC < 5. The non-low prognosis patients: group 5: AFC ≥ 5, previous number of oocytes retrieved > 9 oocytes; group 6: AFC ≥ 5, no previous ovarian stimulation. Intervention(s): None. Main Outcome Measure: The primary outcome was cumulative live birth rate (CLBR). Result(s): The CLBR in group 1 (44.6%) was slightly higher than in group 3 (35.5%, OR 0.9, 95% CI 0.7-1.2) without significant statistical difference. The CLBR in group 2 (24.5%) was significant lower than in group 1 (OR 0.6, 95% CI 0.4-0.8) and CLBR in group 4 (12.7%) was the lowest (OR 0.4, 95% CI 0.3-0.6). In non-poor prognosis patients, the CLBR in the patients with previous IVF failure (group 5, 53.5%) was a slight higher than the reference group 1(OR 1.3 95% CI 0.9, 1.7), while the CLBR in the highest CLBR (66.9%, OR 2.0, 95% CI 1.6, 2.4) was originated from the first IVF patients with good ovarian reserve. Conclusion(s): The CLBRs and implantation rates in the young women (group 3) with diminished ovarian reserve was similar in those young women (group 1), and was significantly higher than in advanced age women with a fair ovarian reserve (group 2). Though patients in group 2 had better ovarian reserve, more oocytes and more embryos, the pregnancy outcome was inferior to that of group 3 patients with poorer ovarian reserve, fewer oocytes and fewer embryos.